DEVELOPING SCRAMBLE GAME MEDIA TO TEACH VOCABULARY SKILL ON DESCRIPTIVE TEXT FOR VII GRADE STUDENTS OF MTS SYEKH SUBAKIR 2 SUMBERASRI - Yuli Anjar Wati; Ahmad Saifudin; Istina Atul Makrifah (PROJECT (Professional Journal of English Education), 2023)
This study aims to the developing scramble game media to teach vocabulary skill on descriptive text. Base on the result of interviews with English teacher and students are lacking in vocabulary. The researcher used the R&D model by ADDIE because ADDIE model. The ADDIE research and development procedure basically consists of five stages, namely analysis, design, development, implementation and, evaluation. The research instruments and data collection techniques in this study used  filed notes, interview guideline, and questionnaires. The results of the research show that used scramble game is powerful for adding vocabulary to MTs Syekh Subakir 2 Sumberasri. This is evidenced by the results of the questionnaires distributed to students after using scramble game media in descriptive lessons to get a total score of 96% from the results of a questionnaire of 21 students, which means that this media is very good for used in increasing English vocabulary. Students find it easier to remember the meaning of new vocabulary and could improve learning activities, especially in adding English vocabulary. Keywords:  ADDIE; Vocabulary; Scramble Game